Dampak Kolam Retensi Seri Terhadap Puncak Banjir Daerah Aliran Batang Kuranji - Februarman, Februarman; Daoed, Darwizal; Syahputra, Aldino (Jurnal Bangunan, Konstruksi & Desain, 2024)
Flooding is a natural phenomenon in the form of water inundating land and can cause harm to humans. Floods can be caused by high rainfall, limited riverbed capacity, and topography and drainage conditions. One of the rivers that causes flooding in the city of Padang is the Batang Kuranji (Kuranji River), especially in the downstream part. Therefore, an environmentally friendly flood control system is needed that can reduce flood peaks downstream, namely by creating several retention ponds. This research was conducted to examine the effect of serial retention ponds on reducing flood peaks in the middle section of Batang Kuranji. Retention ponds are placed on the left and right sides of the river on the section from the Gunung-Nago weir to the Kuranji Bridge on the Padang-Bypass road. The estimated flood discharge in the Gunung-Nago Sub-watershed is 547 m3/s for a 10-year return period with a watershed area of ​​124 km2. The series retention pond simulation appears to be very effective in reducing peak flood discharge by 52% with a pond area of ​​0.8 million m3. Even though the return period is 100 years, the effectiveness percentage is 34%. Suggestions to stakeholders so that the pond can function properly require regular maintenance and dredging,